2015
DOI: 10.1002/aelm.201500052
|View full text |Cite
|
Sign up to set email alerts
|

Giant Electric Energy Density in Epitaxial Lead‐Free Thin Films with Coexistence of Ferroelectrics and Antiferroelectrics

Abstract: lowest energy density. [4][5][6] To improve this, much attention has been particularly paid to antiferroelectric ceramics such as PZ, [ 7,8 ] PLZT, [ 9,10 ] PZN-PMN-PT, [ 4 ] PLZST, [ 4 ] etc., since they normally have higher energy density than ferroelectric and paraelectric ceramics at comparable electric fi eld. [ 2 ] The energy density in bulk ceramics is usually less than 1 J cm −3 because of the limitation of low dielectric breakdown strength (<100 kV cm −1 ). [ 11,12 ] With the development of high-quali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
129
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 217 publications
(131 citation statements)
references
References 33 publications
2
129
0
Order By: Relevance
“…W of the BTO100 film is 5.6 J cm comparable to the highest reported W values from lead-based materials (Fig. 7) [76]. Compared with the BNLBTZ film, our films have simple compositions which means they are easier to process.…”
Section: ∆ C Crtsupporting
confidence: 50%
See 1 more Smart Citation
“…W of the BTO100 film is 5.6 J cm comparable to the highest reported W values from lead-based materials (Fig. 7) [76]. Compared with the BNLBTZ film, our films have simple compositions which means they are easier to process.…”
Section: ∆ C Crtsupporting
confidence: 50%
“…Dielectric capacitors are a promising technology for energy storage devices in high-power applications because of their high-power density, fast charge/discharge time (< 1 μs), low cost, and high thermal and mechanical stability [72][73][74][75][76]. The energy density (W) of a dielectric material is given by…”
Section: ∆ C Crtmentioning
confidence: 99%
“…In high-quality ferroelectric/antiferroelectric thin films the energy storage density is much higher than that of ceramics due to the enhanced dielectric breakdown strength. For example, a very high energy storage density of 154 J/cm 3 at 218MV/m was achieved in the antiferroelectric film (Bi 1/2 Na 1/2 ) 0.9118 La 0.02 Ba 0.0582 (Ti 0.97 Zr 0.03 )O 3 [2], and recently Bin Xu et al [3] predicted via first principle calculations an energy storage density of 100-150 J/cm 3 in the lead free Bi 1−x R x FeO 3 system. However, from a practical point of view, the energy density is determined by the processing method and quality of the film as failure is often driven by flaws.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, the Pnma state in ABO 3 perovskites is known to possess antipolar motions of its A cations and recent studies found that it can also adopt the double polarization-vs.-electric field hysteresis loop in some materials 13,14 that is characteristics of antiferroelectrics 15 -therefore suggesting that Pnma states in some perovskites can hold promise towards the design of energy storage devices with high energy densities and efficiencies. [16][17][18][19][20][21][22] Interestingly, all the aforementioned works on trilinear energetic couplings have been aimed at revealing and understanding resulting static properties. In other words, the effect of these original trilinear couplings on dynamics have been left out so far and are thus basically unknown, to the best of our knowledge.…”
Section: Introductionmentioning
confidence: 99%